Characterization and antimicrobial analysis of rice starch-chitosan blend biodegradable film with addition of cinnamon essential oil - Mohd Fouzzi, Mohd Jabar (2010)
This study will be focusing on fabrication of composite biodegradable film from rice starch-chitosan blends with addition of cinnamon oil. The film was characterized in term of morphology, physical, chemical and also the antimicrobial analysis. For solution preparation, rice starch was dissolved in distilled water at concentrations of 2g/100 ml by heating the mixtures on hot plates and stirred until it gelatinized at 85°C for 5 minute. The mixtures were then cooled to 27°C. The chitosan solution was prepared by dispersing 2 g of chitosan in 100 ml of 1% v/v acetic acid. 1 ml of cinnamon essential oil was added to the mixture. Polyethylene glycol (PEG) 400 was added as a plasticizer. The solution was cast onto flat glass plate. The thickness of the film was adjusted using a casting knife. The film was left to dry at room temperature before peeled off. The fabricated film was analyzed and characterized using Scanning electron microscopes (SEM), Fourier transform infrared Spectroscopy (FTIR), Thermogravimetric analyzer (TGA) and Differential scanning calorimeter (DSC). The antimicrobial analyses were performed using Zone inhibition assay and Liquid culture test. As a conclusion, the rice starch-chitosan blend biodegradable film with addition of cinnamon essential oil shows the highest thermal resistant compared to control film. Other than that, the film also shows the greatest antimicrobial activity towards E. co/i and B. subti/is.